Pemanfaatan Teknologi Informasi dalam Edukasi Literasi Digital untuk Peningkatan Keamanan Data dan Pencegahan Kejahatan Siber di Masyarakat Rawang Panca Arga - Zulfa Ar Rahman (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The utilization of information technology in digital literacy education has become increasingly important due to the growing threat of cybercrime. This research aims to analyze the impact of digital literacy education on improving data security and preventing cybercrime within the community. Using a qualitative approach, this study identifies the role of information technology in raising public awareness and understanding of the importance of protecting personal data online. The findings reveal that digital literacy education, supported by information technology, can significantly reduce the risk of cybercrime. Communities that are educated in digital literacy are better equipped to face cybersecurity challenges and safeguard the integrity of their data. This education also provides practical guidelines for using digital devices safely and ethically.